Characteristics Of The Knowledge Service System On The Behavior Of Preventing The Transmission Of COVID-19 In The City Of Ternate - Kurniawan, Didik (Publisher Cv. Inara, 2022)
Since the COVID-19 pandemic hit the whole world including Indonesia, there has been a change in habits in living life for all parties, including health service providers, especially hospitals, which are the last bastion in the fight against the COVID-19 pandemic. The type of research used in this study is a descriptive quantitative method, which is carried out on a set of objects which usually aims to see the characteristics in order to determine the extent of knowledge, attitudes, family support and use of media towards the knowledge service system about the behavior of preventing transmission of Covid-19 patients in Indonesia. community in Ternate City. The population in this study was all Covid-19 data recorded in medical records at the City Health Center in 2020, as many as 118 civid 19 sufferers. The sampling technique was carried out by the total sample method. The research was carried out in 2020. The results of the univariate analysis describe the distribution of respondents based on demographic characteristics (gender, education level, occupation, knowledge, family support attitudes and preventive behavior), with COVID-19 disease.